2003
DOI: 10.1097/01.hjr.0000072574.13775.6d
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Atherosclerotic Effects of Statins: Lessons from Prevention Trials

Abstract: Statins are best-known for their lipid-lowering effects and have been shown to significantly impact the natural progression of coronary atherosclerosis. The mechanism through which they exert this effect is thought to be primarily due to their ability to reduce low-density lipoprotein cholesterol levels. However, there is increasing evidence that statins exert a myriad of other beneficial effects on the vascular wall, thus altering the course of atherosclerotic disease. This article will review the prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(24 reference statements)
1
6
0
Order By: Relevance
“…Of course, anti-atherosclerotic effects of statins revealed in many prospective clinical trials may be considered; however, statins were never recognized as the drugs indicated just for direct treatment or prevention of atherosclerosis [1520]. They are used predominately in the course of hypolipidemic therapy, and the effects of treatment are estimated by success in reaching the target level of LDL cholesterol, but not the regression of atherosclerotic lesion or IMT.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, anti-atherosclerotic effects of statins revealed in many prospective clinical trials may be considered; however, statins were never recognized as the drugs indicated just for direct treatment or prevention of atherosclerosis [1520]. They are used predominately in the course of hypolipidemic therapy, and the effects of treatment are estimated by success in reaching the target level of LDL cholesterol, but not the regression of atherosclerotic lesion or IMT.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Also, BH 4 has been shown to delay plaque formation in the ApoE Ϫ/Ϫ mouse 14 that presents low BH 4 levels. The detrimental effects of high cholesterol on aortic BH 4 levels were shown in hypercholesterolemic rabbits.…”
mentioning
confidence: 99%
“…Statins act by inhibiting the conversion of HMG-CoA to mevalonate, which is a rate-limiting step in the cholesterol biosynthesis pathway and thus lowering the LDL-cholesterol in the blood (2). Previous clinical trials have demonstrated that statins are able to substantially decrease cardiovascular-associated morbidity and mortality in patients with and without coronary disease (35). Since serum cholesterol levels have been closely associated with coronary artery disease (6), it was initially hypothesized that the ability of statins to lower cholesterol levels was the predominant mechanism underlying the observed reduction in the risk of cardiovascular diseases (7).…”
Section: Introductionmentioning
confidence: 99%